STATUS OF AVIFAUNA IN CURZON HALL PREMISES UNIVERSITY OF DHAKA, BANGLADESH - Akash, Muntasir; Hossain, Anwar; Chowdhury, Gawsia Wahidunnessa; Mahmud, Humayra; Islam, Anwarul (Ecoprint: An International Journal of Ecology, 2014)
In order to estimate the diversity and status of avian species of Curzon Hall premises, University of Dhaka, Bangladesh, a study was conducted from January 2012 to January 2014. A total of 50 species of birds belonging to 30 families under 12 orders were recorded of which, regarding the relative abundance, 29 were common and 21 were uncommon. Twenty five species, in total, were identified as breeding residents, 13 as non-breeding residents and 12 as migrants. Of all the species identified from the study site, one was Critically Endangered (Alexandrine Parakeet Psittacula eupatria) and six were new for the campus (Taiga Flycatcher Ficedula albicilla, Indian Silverbill Lonchura malabarica, Ashy Drongo Dicrurus leucophaeus, Eurasian Wryneck Jynx torquilla, Pied Cuckoo Clamator jacobinus, Lesser Whistling Duck Dendrocygna javanica). Passerines were the dominating group as represented by 27 species from 16 different families. Species richness was in the highest peak in the late winter and early spring and comparatively less in other seasons.DOI: http://dx.doi.org/10.3126/eco.v20i0.11324Ecoprint: An International Journal of EcologyVol. 20, 2013Page : 1-8